2002
DOI: 10.1074/jbc.m204669200
|View full text |Cite
|
Sign up to set email alerts
|

Placental Alkaline Phosphatase Is Efficiently Targeted to Rafts in Supported Lipid Bilayers

Abstract: Evidence is growing that biological membranes contain lipid microdomains or "rafts" that may be involved in processes such as cellular signaling and protein trafficking. In this study, we have used atomic force microscopy to examine the behavior of rafts in supported lipid bilayers. We show that bilayers composed of equimolar dioleoylphosphatidylcholine and sphingomyelin spontaneously form rafts, which are detectable as raised features. A comparison of the extents of protrusion of the rafts in monolayers and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
161
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(180 citation statements)
references
References 25 publications
(18 reference statements)
16
161
1
2
Order By: Relevance
“…These results differ from those recently obtained with PLAP in which, using SLB b s, only one-fourth of the total AP-GPI was found, with significant aggregation, in the l o domains at room temperature [18]. The conclusions of this last paper, in which fluorescence correlation spectroscopy and confocal fluorescence were also used, also differ from the previous one on PLAP [82]. They were however close to those obtained by the same group on GUVs using fluorescence markers [52].…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainscontrasting
confidence: 91%
See 3 more Smart Citations
“…These results differ from those recently obtained with PLAP in which, using SLB b s, only one-fourth of the total AP-GPI was found, with significant aggregation, in the l o domains at room temperature [18]. The conclusions of this last paper, in which fluorescence correlation spectroscopy and confocal fluorescence were also used, also differ from the previous one on PLAP [82]. They were however close to those obtained by the same group on GUVs using fluorescence markers [52].…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainscontrasting
confidence: 91%
“…To summarize, these data strongly suggested that the GPI anchor might contribute to the formation of its most appropriate membrane environment in terms of hydrophobic length and lipid order parameter [40]. Like for BIAP, PLAP has been visualized in the gel SM enriched ordered phase in SLB b s made of DOPC/SM [82]. Notice that the BIAP dimers are first visualized at the periphery of the ordered domains (arrows in b) then found in the center of domains for longer incubations (arrows in c).…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainsmentioning
confidence: 87%
See 2 more Smart Citations
“…They behave as non-cooperative allosteric enzymes in which the stability and the catalytic properties of each monomer are controlled by the conformation of the second subunit [476]. A dimeric structure has also been suggested after incorporation of the protein into supported lipid bilayers and analysis by atomic force microscopy [477]. Each catalytic site contains three metal ions, two Zn 2+ , and one Mg 2+ that are necessary for catalytic activity.…”
Section: Alkaline Phosphatasesmentioning
confidence: 99%